2004
DOI: 10.1111/j.1533-2500.2004.04206.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profile and Efficacy of a Fentanyl Transdermal Delivery System for Acute Postoperative Pain after Intra‐abdominal Gynecologic Surgery for Cancer

Abstract: The transdermal therapeutic system for administration of fentanyl, combined with epidural administration of a nonopioid analgesic such as bupivacaine is effective in controlling postoperative pain after gynecologic surgery. Additionally, the safety/tolerability of this regimen was similar to placebo plus bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…10 However, in most of these cases the specific causes are difficult to evaluate because of the concomitant use of other opioids such as morphine, [29][30][31][32][33][34][35] which may enhance respiratory depression. 10 Also, in these cases surgeries were performed under general anesthesia and TDF was delivered at much higher rates (ranging 50-100 mg/h) than in the present study (12 mg/h). A recent study using the same TDF patch as used in our study (Durogesic TTS) reported analgesic efficacy and safety of this transdermal system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 However, in most of these cases the specific causes are difficult to evaluate because of the concomitant use of other opioids such as morphine, [29][30][31][32][33][34][35] which may enhance respiratory depression. 10 Also, in these cases surgeries were performed under general anesthesia and TDF was delivered at much higher rates (ranging 50-100 mg/h) than in the present study (12 mg/h). A recent study using the same TDF patch as used in our study (Durogesic TTS) reported analgesic efficacy and safety of this transdermal system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have administered premedication with TDF 1-2 h before surgery; this resulted in mostly favorable outcomes. 10,[29][30][31][32][33] In our study, TDF was administered 2 h preoperatively. However, our results suggest the need for further evaluation of earlier premedication with TDF and/or additional adjuvant medication to efficiently cope with early postoperative pain after PRK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El fentanilo tiene el mismo metabolismo hepático que el resto de los opiá-ceos pero su metabolito es inactivo. La presentación en sistemas de liberación transcutánea se ha empleado en el manejo del dolor postoperatorio, a dosis de 50 microgramos/hora, aunque debido a su farmacocinética no es una elección habitual (7). El tiempo que transcurre hasta conseguir un efecto máximo es de 12 a 48 horas (8).…”
Section: Discussionunclassified
“…However, although clinical evaluation revealed to some extent benefit of all T drugs tested, the laboratorial data revealed that administration of T fentanyl alone (FenG) resulted in plasma noradrenaline decrease at 6-h compared to itself at the 0-h. Although the minimum effective concentration of T fentanyl in serum (0.63 ng/mL) was achieved at 11.3 ± 4.9 hours after application 11 , fentanyl as a cream preparation took less than six hours, and was indirectly supported by the decreased plasma noradrenaline serum levels. In addition, the association of T fentanyl with clonidine resulted in plasma noradrenaline decrease even at 3-and 6-h, compared to either drug alone or to the other groups, corroborating to the clinical data.…”
Section: Discussionmentioning
confidence: 99%